Laboratory recommendations for scoring deep molecular responses following treatment for chronic myeloid leukemia - Cross, N C P; White, H E; Colomer, D; Ehrencrona, H; Foroni, L; Gottardi, E; Lange, T; Lion, T; Machova Polakova, K; Dulucq, S; Martinelli, G; Oppliger Leibundgut, E; et al. (Leukemia, 2015)
Treatment of chronic myeloid leukemia (CML) with tyrosine kinase inhibitors has advanced to a stage where many patients achieve very low or undetectable levels of disease. Remarkably, some of these patients remain in sustained remission when treatment is withdrawn, suggesting that they may be at least operationally cured of their disease. Accurate definition of deep molecular responses (MRs) is therefore increasingly important for optimal patient management and comparison of independent data sets. We previously published proposals for broad standardized definitions of MR at different levels of sensitivity. Here we present detailed laboratory recommendations, developed as part of the European Treatment and Outcome Study for CML (EUTOS), to enable testing laboratories to score MR in a reproducible manner for CML patients expressing the most common BCR-ABL1 variants.
Keywords: Europe; polymerázová řetězová reakce; Polymerase Chain Reaction; výsledek terapie; Reproducibility of Results; bcr-abl fúzní proteiny; lidé; Calibration; Evropa; chronická myeloidní leukemie; Treatment Outcome; stanovení celkové genové exprese; regulace genové exprese u leukemie; Genetic Variation; kalibrace; reprodukovatelnost výsledků; limita detekce; Gene Expression Regulation, Leukemic; Limit of Detection; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; Fusion Proteins, bcr-abl; Protein-Tyrosine Kinases; genetická variace; Gene Expression Profiling; tyrosinkinasy; Humans